Preterm Birth Prevention in Appalachia: Restructuring Prenatal Care to Address Rural Health Disparities and Establish Perinatal Health Equity (Mary Ann Liebert, 2021)
Purpose: This perspective piece reflects off previously published qualitative work to explore (1) themes surrounding equitable prenatal care in Appalachia and (2) strategies to restructure care delivery in a population with disparate rates of preterm birth (PTB). Methods: This study reflects in-depth interviews with 22 Appalachian women who experienced PTB and 14 obstetric providers. Results: Our findings underscore the need for greater cultural humility in prenatal care, heightened awareness of social determinants of health, and strategic planning to establish equity in birth outcomes. Conclusion: Prenatal care must undergo a paradigm shift to include a comprehensive discussion of cultural humility, social disparities, and health equity.